La economía de la innovación: del legado de los clásicos a la economía de la complejidad - Antonelli, Cristiano (2006)
During the last forty years, economics of innovation has emerged as a distinct area of enquiry at the cross roads of the economics of growth, industrial organization, regional economics and the theory of the firm. It has become a well identified area of competence in economics, specializing not only in the analysis of the effects of the introduction of new technologies, but also and mainly in understanding technological change as an endogenous process. As the result of the interpretation, elaboration and evolution of different fields of analysis in economic theory, innovation is viewed as a complex, path-dependent process characterized by the interdependence and interaction of a variety of heterogeneous agents, able to learn and react creatively with subjective and procedural rationality.